A survey on occupants’ satisfaction in the design of public low-cost housing in Selangor / Mohammad Amram Awang Omar - Awang Omar, Mohammad Amram (Faculty of Architecture, Planning and Surveying, 2013)
This dissertation was aimed to study about a survey on occupants’ satisfaction in the design of public low-cost housing in Selangor. The study has specific aim and objectives to achieve which is the main part of the research. The primary aim of this study is to identify level of satisfaction of occupants about design of low-cost house. Meanwhile, the second objective is to know efficiency of maintenance at the low-cost housing and the third objective to recommend improvement on the design and maintenance of low-cost apartment in Malaysia. This dissertation therefore contained an analysis of the occupants’ satisfaction of public low-cost housing. The questionnaire and interview distributed to public low-cost housing. From the questionnaire distributed, 90 respondents participate which include 30 respondents Ken Rimba Apartment, 30 respondents from Klang Jaya Apartment and balance 30 from Permai Indah Apartment. Interview distributed, interview were carried out with Local Authorities which are Majlis Perbandaran Klang and Majlis Bandaraya Shah Alam and several occupants in the case study building.The result indicated 88% of respondents are concerned on building design of low-cost house. However, 12% of the respondents are dissatisfied with parking and store provided in low-cost house. The study recommends improvement on the future design low-cost housing